Analisis Kesulitan Siswa Dalam Memahami Materi Pecahan Campuran Di Kelas V SDIP YLPI Riau - Tri Wahyuni; Siti Quratul Ain; Fitriyeni (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to find out how difficult students are in understanding mixed fractional material in class V SDIP YLPI Riau.This study uses qualitative research with descriptive methods. This study used 4 data collection techniques, namely tests, observations, interviews, and documentation. The data analysis technique used is according to Miles and Huberman. The results showed that there were several difficulties of students in understanding mixed fractional material in class V SDIP YLPI Riau, namely first students' difficulties in understanding concepts, second students' difficulties in using principles. Third, students' difficulties in solving verbal problems. The teacher's efforts to overcome the difficulties of learning mathematics are providing guidance on teaching remedia, providing learning motivation, using learning media, providing sufficient practice and teaching multiplication to students.